Unusual site of pyogenic granuloma: Case report - Ramasundram, Shankar; Mohamad, Irfan; Kumarasamy, Sivakumar; Kamara Ambu, Valuyeetham (Elsevier, 2017)
Pyogenic granuloma (PG) is a relatively common benign vascular lesion of the skin and mucosa. While PG of the oral cavity and nasal cavity is a well-known entity, oropharyngeal localization has never been reported. We present a 56-year-old woman with sore throat, hemoptysis and dysphagia due to a tumor at oropharynx. Initial suspicion of malignancy was ruled out by excision biopsy of the lesion. Histologically it was reported as pyogenic granuloma of the oropharynx.